An Analysis of Clipping Words on Whatsapp Group Chat - Ikhsan Ikhsan; Dohra Fitrisia; Chairina Nasir (Research in English and Education Journal, 2021)
Clipping word occurs whenever a word is shortened by deleting parts of the base word. Furthermore, clipping is the word formation process wherein words are reduced or shortened without changing the meaning. This research was about an analysis of clipping words on WhatsApp group chat. The aims of this study were to find out the types of clipping word that frequently used by WhatsApp users. The clipping words used was in Indonesian language. The primary sources of the data in this research were the screen shoot of WhatsApp group chats of KBM ESA USK and HMI Komsat FKIP USK. The purposive sampling technique is used by the researcher in order to select the sample of this research as the research thought it was more appropriate to be carried out when research requires special criteria in accordance with the research objectives in order to solve the research problems and can provide more representative value. Five males and 5 females were selected as the research samples. Type of this research was descriptive qualitative research which is purely data-derived in that codes are generated from the data in the course of the study. Researcher analysed four types of clipping words adapted from Hosseinzadeh (2014, p. 19) which are being the object of this research, there are Back Clipping, Fore Clipping, Middle Clipping and Complex Clipping used on WhatsApp group chat. The result showed that the most dominant type of clipping word used was complex clipping word (61.7%) then followed by back clipping word (28%), fore clipping word (8.7 %) and middle clipping word 1.6%. it was concluded that the most dominant clipping word used was complex clipping word.